Restitusi bagi Korban Kekerasan Seksual Anak: Studi Komparatif Sistem Hukum Indonesia dan Malaysia - Setyawati Setyawati; Khairul Mannan; Fikry Fathurrahman; Muhammad Rafi Irwanzah; Aburizal Fatwa Ramli (Jurnal Litigasi Amsir, 2026)
This study examines the protection of recovery rights for child victims of sexual violence in Indonesia and Malaysia through a normative and comparative analysis of the applicable legal frameworks. The research is motivated by the need to assess the extent to which the criminal justice systems in both countries not only punish offenders, but also guarantee restitution or compensation for victims and their families. It adopts a case study approach, focusing on the Natuna District Court decision in Indonesia and the Zara case in Malaysia, and is complemented by a doctrinal review of relevant legislation, including Indonesia’s Law on Sexual Violence Crimes (UU TPKS) 2022 and Supreme Court Regulation, as well as Malaysia’s Child Act (Amendment) 2016, Sexual Offences Against Children Act 2017, and Criminal Procedure Code. The analysis shows that Indonesia has more explicitly integrated the right to restitution into its juvenile criminal justice system, so that financial recovery for victims forms part of the operative judgment and is supported by clear enforcement mechanisms. By contrast, the Malaysian legal system is characterised by severe penal sanctions against perpetrators but has not consistently operationalised victim compensation mechanisms, as illustrated by the Zara case, in which the victim’s family did not receive financial redress through the court’s decision. These findings indicate that, although both countries have made progressive strides in child protection, Indonesia is comparatively more advanced in adopting restorative justice principles, whereas Malaysia still needs to strengthen the victim-recovery dimension to achieve a more balanced legal protection between punishment and restoration.